Ways to optimize teaching a Foreign Language at Higher Education Institutions - Miahka, M. (Problems of Engineer-Pedagogical Education, 2022)
The article attempts to analyze the main methods of the new material presentation and rehearsal in the foreign language classes at higher education institutions in order to optimize the learning process. The author emphasizes that optimization is a natural stage in the development of any science, which makes it necessary for the teacher to seek certain measures to create ideal conditions for students’ training, education and development. The article specifies that cognitive activity of a student during the stages of familiarization and acquisition of the new foreign language material should become the main course of the teacher’s action when modeling a class. While presenting to students the vocabulary and grammatical structures to be mastered, the teacher also determines the logic of building their communication. The article offers examples of technologies, by means of which it is reasonable to carry out procedures of actualization and activation while working with foreign language vocabulary. One of the modern developments related to the direction of art technologies for vocabulary activation in a foreign language class (collaging as a support for speaking with authentic materials) is presented in the article. The potential of employing modern information technologies used in the process of teaching foreign languages to students at higher education institution is revealed. In the conclusions, the author notes that intensive methods of new foreign language material presentation and elaboration as well as the use of multimedia technologies present methodological opportunities for higher education teachers to enjoy prospects of intensification of foreign language teaching in higher education institutions for the purpose of developing creative personality of the future specialist, capable of self-development, self-education and innovative activity. Collaboration between a teacher and a student in a foreign language class is designed to contribute to the development of students’ independence in working with the new lexical material. An indicator of the effectiveness of a foreign language class is the independence and activity of students in foreign language activities. Ways to optimize the process of foreign language teaching implement the practical, developmental and educational aspects of the learning objectives.